(untitled) (Journal of the College of Education for Women, 2019)
Colors are universal, and throughout the ages, they have been associated withvarious religious, social and spiritual meanings. They symbolize a galaxy of thingsto designate certain ideas or symbols that are sometimes contradictory.The present study is an attempt to investigate colors, their meanings andsymbolism, and the approaches to translating color idioms from English intoArabic. It fathoms one of the thorny areas for translation theorists let alonepractitioners. Various definitions, classifications of types and symbolism acrosscultures are provided. After reviewing idioms and methods of translating them, asurvey of 114 sentences that include color idioms was conducted to see whichmethod is mostly adopted by professionals. The survey has revealed that, amongthe methods available for the translator, the most common strategy in translatingcolor idioms from English into Arabic is paraphrase, followed by loan translation.In addition, the equivalent effect principle sought by Nida (1964) would not beachieved and the color element found in the source language is lost in translation,simply because it has neither linguistic nor cultural correspondent equivalent in thetarget language.